Tinjauan Yuridis Penyelesaian Kredit Macet terhadap Profitabilitas Bank - Amin Widjaja; Tiyar Cahya Kusuma; Gindo L Tobing (Syntax Corporation, 2023)
The definition of credit according to Law No. 10 of 1998 concerning Banking, it is stated that credit is the provision of money or bills that can be likened to it, based on an agreement or loan agreement between a bank and another party that requires the borrower to pay off its debt after a certain period of time with interest / margin, ROE is a ratio used by banks to measure the ability of banks to generate net profit. ROE can be measured by comparing profit after tax with the bank's own capital. The higher the ROE, the higher the level of profit that a bank will achieve and the less likely the bank is in trouble. If bad loans increase, the profit obtained by the bank will decrease because the bank must provide reserves to cover losses caused by bad loans Bad loans involving State-Owned Banks.usually bad loans have been attempted for collection / settlement in a family manner but are unsuccessful, the bank will submit the settlement through BUPLN, henceforth will conduct auctions / sales of collateral objects unless If the Bank has obtained a